National scale-up of tuberculosis–human immunodeficiency virus collaborative activities in Myanmar from 2005 to 2016 and tuberculosis treatment outcomes for patients with human immunodeficiency virus-positive tuberculosis in the Mandalay Region in 2015. (19th January 2018) - Theingi, Phyo; Harries, Anthony D; Wai, Khin Thet; Shewade, Hemant D; Saw, Saw; Win, Than; Thein, Saw; Kyi, Myo Su; Nyunt Oo, Htun; Aung, Si Thu
Abstract: Background: HIV-associated TB is a serious public health problem in Myanmar. Study objectives were to describe national scale-up of collaborative activities to reduce the double burden of TB and HIV from 2005 to 2016 and to describe TB treatment outcomes of individuals registered with HIV-associated TB in 2015 in the Mandalay Region. Methods: Secondary analysis of national aggregate data and, for treatment outcomes, a cohort study of patients with HIV-associated TB in the Mandalay Region. Results: The number of townships implementing collaborative activities increased from 7 to 330 by 2016. The number of registered TB patients increased from 1577 to 139 625 in 2016, with the number of individuals tested for HIV increasing from 432 to 114 180 (82%) in 2016: 10 971 (10%) were diagnosed as HIV positive. Uptake of co-trimoxazole preventive therapy (CPT) and antiretroviral therapy (ART) nationally in 2016 was 77% and 52%, respectively. In the Mandalay Region, treatment success was 77% and mortality was 18% in 815 HIV-associated TB patients. Risk factors for unfavourable outcomes and death were older age (≥45 years) and not taking CPT and/or ART. Conclusion: Myanmar is making good progress with reducing the HIV burden in TB patients, but better implementation is needed to reach 100% HIV testing and 100% CPT and ART uptake in TB–HIV co-infected patients.